2022
DOI: 10.3390/diagnostics12102405
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Assisted Automated Assessment of Thalassaemia from Haemoglobin Electrophoresis Images

Abstract: Haemoglobin (Hb) electrophoresis is a method of blood testing used to detect thalassaemia. However, the interpretation of the result of the electrophoresis test itself is a complex task. Expert haematologists, specifically in developing countries, are relatively few in number and are usually overburdened. To assist them with their workload, in this paper we present a novel method for the automated assessment of thalassaemia using Hb electrophoresis images. Moreover, in this study we compile a large Hb electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As the hemorrhage is only segmented from the images, it can be considered instance segmentation. This study used a U-Net (encoder-decoder)-like convolutional neural network (CNN) to instance segment the area of hemorrhage presented in a CT image since it performed better than other deep learning networks [21].Several pre-trained models trained on the ImageNet dataset served as encoders in segmentation tasks [22]. A pre-processing step was first performed on the raw data before different variants of the U-Net model were trained to predict ICH masks.…”
Section: Methodsmentioning
confidence: 99%
“…As the hemorrhage is only segmented from the images, it can be considered instance segmentation. This study used a U-Net (encoder-decoder)-like convolutional neural network (CNN) to instance segment the area of hemorrhage presented in a CT image since it performed better than other deep learning networks [21].Several pre-trained models trained on the ImageNet dataset served as encoders in segmentation tasks [22]. A pre-processing step was first performed on the raw data before different variants of the U-Net model were trained to predict ICH masks.…”
Section: Methodsmentioning
confidence: 99%
“…Phenylacetylglycine, creatine and indole-3-lactic acid were significantly up-regulated in the EFI, compared with the four NDRDs groups (Figure 3A(b-d)). The specific procedure used 80% of the above 50 samples as the training set [39] (n EFI = 8, n NDRDs = 32). The results showed that the classification model consisting of these three candidate differentials based on 100 cross-validations had an AUC value equal to 1 (Figure 3B(a)).…”
Section: Classification Model Screening and Verification In Efi Plasm...mentioning
confidence: 99%
“…Also, a combination of SVD [8] and PCA [41] as a feature reduction technique with data balancing technologies such as SMOTE and ADASYN is used. Filtering and thresholding, object detection, erosion and dilation, boundary detection, and lane extraction [42] are used for image datasets. DSIFT and DTL2 [43] are used for features of images.…”
Section: Preprocessing Techniques Reviewmentioning
confidence: 99%
“…Automated evaluation of thalassemia has been studied using a unique deep-learningbased method [42] for thalassemia screening. The main goal of the project is to automatically obtain the tracks from electrophoresis envision strips and classify individuals as normal or abnormal with thalassemia.…”
Section: Classifiers For Beta Thalassemiamentioning
confidence: 99%